Spectrophotometric Determination of Aprepitant in Bulk and Pharmaceutical Dosage Forms Using Bromocresol Green as Chromogenic Reagent - Souri, Effat; Abbasi, Amin; Amanlou, Massoud; Tehrani, Maliheh Barazandeh (Asian Journal of Chemistry, 2018)
Aprepitant is a substance P/neurokinin 1 receptor antagonist, which is used for preventing both acute and delayed emesis. In the present study a simple and accurate spectrophotometric method has been developed for quantitative determination of aprepitant in bulk and pharmaceutical dosage forms based on the formation of ion-pair complex between the drug and bromocresol green. The 1:1 yellow colour aprepitant-bromocresol green (BCG) ion-pair complex was formed in buffer solution at pH = 4, extracted with chloroform and measured at 413 nm. The optimum reaction conditions such as pH, reagent amount, extracting solvent and stoichiometry of the ion-pair complex were investigated. The developed method showed excellent linearity over the concentration range of 150-500 μg/mL with acceptable correlation coefficient (r2 = 0.998), precision (CV < 3.67 %) and accuracy (Error < 3.46 %). The proposed method was successfully applied for determination of aprepitant in capsule dosage forms and no interference from excipients was observed.